THE ACCEPTANCE OF BAKED GETUK (CASSAVA CAKE) WITH RICE BRAN AND RED BEANS SUBSTITUTION AS HIGH FIBER SNACK FOR ELDERLY - Ali Iqbal Tawakal; Annis Catur Adi; Dominikus Raditya Atmaka (Media Gizi Indonesia, 2021)
Rice bran and red beans are one of food items that contain high dietary ﬁber and can be processed into traditional snacks such as baked getuk (cassava cake). Elderly needs enough ﬁber to support their metabolism. This study aims to analyze the eﬀect of rice bran and red bean substitution of getuk toward its acceptance and dietary ﬁber contents. This study was an experimental study with a completely randomized design. There were four treatments of rice bran and red beans substitution (F0 = 0% rice bran, 0% red beans); (F1 = 10% rice bran, 13% red beans); (F2 = 13% rice bran, 10% red beans), (F3 = 17% rice bran, 7% red beans). This study further involved 30 untrained elderly and pre- elderly panelists (45–80 years). Acceptance was measured using a hedonic questionnaire on a scale of 1 to 6. Statistical analysis of acceptability diﬀerences was completed using Kruskal-Wallis and Mann-Whitney test with α ≤ 0.05. In results, there were signiﬁcant diﬀerences between F1, F2, F3, and F0 on all characteristics (color, aroma, texture, taste) with p = 0.001, and the acceptance rating from highest to lowest was F3, F2, F1, respectively. The organoleptic test results further showed that the panelists mostly preferred the F3 formula (17% rice bran and 7% red beans). There was no signiﬁcant diﬀerence in dietary ﬁber content between each formula, F1 contains 9.250 grams of dietary ﬁber (30.8% RDA), F2 contains 9.242 grams of dietary ﬁber (30.8% RDA), and F3 contains 9.235 grams of dietary ﬁber (30.7% RDA). This study proved that rice bran and red red beans substitution to getuk improves its ﬁber content and also having good acceptability.